Education and democratic preferences - Alberto Chong; Mark Gradstein (Inter-American Development Bank, Research Department, 2009)
This paper examines the causal link between education and democracy. Motivated by a model whereby educated individuals are in a better position to assess the effects of public policies and hence favor democracy where their opinions matter, the empirical analysis uses World Values Surveys to study the link between education and democratic attitudes. Controlling for a variety of characteristics, the paper finds that higher education levels tend to result in prodemocracy views. These results hold across countries with different levels of democracy, thus rejecting the hypothesis that indoctrination through education is an effective tool in non-democratic countries.
Keywords: I20; I30; Y80; 330; Education; democracy; Bildung; Demokratie; Öffentliche Meinung; Bildungsniveau; Schätzung; Welt